Non-operative outcomes in Chiari I malformation patients. Issue 1 (January 2015) - Killeen, Amy; Roguski, Marie; Chavez, Alexis; Heilman, Carl; Hwang, Steven
Abstract While postoperative outcomes of Chiari I malformation patients have been well-reported, there is a paucity of literature concerning non-operative management in these patients. We retrospectively identified patients with Chiari I malformation who were not recommended for surgery based on lack of clinical objective findings or inconsistent cough headaches and conducted patient follow-up with a prospective telephone survey. Of the 68 patients (mean age at diagnosis 30.1 ± 17.4 years), 72% were female and 31% were pediatric patients (age at diagnosis ⩽18 years). Average follow up was 4.9 ± 2.9 years. Typical presenting symptoms included cough headache, non-specific headache, nausea, ataxia, dysphagia and paresthesias. Overall, 40% of patients who had cough headaches and 61.5% of patients with non-specific headaches reported improvement. The presence of subjective sensory symptoms was significantly associated with less likelihood of cough headache improvement while the presence of a cough headache was also associated with a lower likelihood of improvement in all non-cough symptoms. The pediatric subgroup had a greater rate of improvement with all cases of nausea/emesis and paresthesias improved or resolved at follow-up. Overall 67% of pediatric patients had improved cough headache and 71% had improvement of migraines/diffuse headaches. We found that many symptoms of Chiari I patients from our conservatively managed cohort either improved or remained unchanged over time. However, the presence of cough headaches was a significant negative predictor of concomitant symptom improvement. This further validates the view that patients with cough headaches should be considered for surgical intervention and provides useful information to counsel patients.